2016
DOI: 10.5604/17307503.1222842
|View full text |Cite
|
Sign up to set email alerts
|

Children With Epilepsy: Specific Learning Difficulties

Abstract: SUMMARYThe problems of children and adolescents with epilepsy pose an important challenge for educational systems around the world. Epilepsy is the most common chronic neurological disease, which occurs in up to 1% of children and adolescents. The largest incidence of onset is from early childhood to adolescence, therefore, mostly the emotional, cognitive and social problems experienced by patients coincide with the school period. It is commonly believed, as indicated by research, that some of the children and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 20 publications
0
2
0
Order By: Relevance
“…In this study, a broad definition of disability including different types of disabilities and chronic conditions was used, thus constituting a relatively heterogeneous group of adolescents with disabilities. However, one argument for having this broad definition is that it seems to exist comorbidity between different disabilities and chronic conditions, and in turn with having different forms of learning disabilities (Blood et al, 2003; Kaczmarek et al, 2016; Pavlou & Gkampeta, 2011; Wassenberg et al, 2010). Nevertheless, some of the research presented in the introduction have been conducted with specific types of conditions (e.g., ADHD or diabetes), which may affect the comparability between our results and this type of research.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In this study, a broad definition of disability including different types of disabilities and chronic conditions was used, thus constituting a relatively heterogeneous group of adolescents with disabilities. However, one argument for having this broad definition is that it seems to exist comorbidity between different disabilities and chronic conditions, and in turn with having different forms of learning disabilities (Blood et al, 2003; Kaczmarek et al, 2016; Pavlou & Gkampeta, 2011; Wassenberg et al, 2010). Nevertheless, some of the research presented in the introduction have been conducted with specific types of conditions (e.g., ADHD or diabetes), which may affect the comparability between our results and this type of research.…”
Section: Discussionmentioning
confidence: 99%
“…Compared to adolescents without ADHD, research showed that adolescents with ADHD had lower academic achievements (Kandemir et al, 2014; Owens & Jackson, 2017; Voltas et al, 2014). Research also provides evidence for poor academic achievements among adolescents with epilepsy (Kaczmarek et al, 2016), asthma (Kohen, 2010), and adolescents with diabetes (Persson et al, 2013). Nevertheless, research showed that adolescents with a chronic medical condition did not report lower academic aspirations than their healthy peers (Wisk & Weitzman, 2017).…”
Section: Introductionmentioning
confidence: 99%